Identification of Staphylococcal Hemolysins by an Electrophoretic Localization Technique - Haque, Riaz-Ul (1967)
A technique for identifying and characterizing staphylococcal hemolysins by first separating them electrophoretically in barbital-buffered agar gel (pH 8.4) at 5 ma/cm for 2 hr and then determining their hemolytic activities by exposing them to human, horse, rabbit, and sheep erythrocytes is described. The α-hemolysin produced by a White variant of the Wood 46 strain of Staphylococcus aureus migrated 18 mm towards the cathode, and it lysed horse, rabbit, and sheep erythrocytes, whereas a Clear variant of the Wood 46 strain of S. aureus produced a lysin which migrated similarly to the α-hemolysin but lysed only rabbit cells. This latter lysin was tentatively named α(1)-lysin. This strain of S. aureus also produced β-hemolysin which migrated 36 mm towards the cathode and lysed sheep cells. β-Hemolysin produced by some strains of S. aureus showed considerable tailing during electrophoresis, whereas β-hemolysin produced by other strains of S. aureus migrated as a well-defined peak. A lysin migrating 11 mm towards the anode was probably δ-lysin. It was, however, not produced in sufficient concentration when the cultures were grown in semisolid medium.